Inovasi Mi Basah Bebas Gluten Berbahan Tapioka dan Tepung Beras dengan Penambahan Tepung Ubi Ungu - Vannessa Mae Putriyana; Lilis Sulandari; Ita Fatkhur Romadhoni; Andika Kuncoro Widagdo (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
This study aims to develop a gluten-free wet noodle product by utilizing a combination of tapioca flour and rice flour, as well as the addition of purple sweet potato flour as a natural source of anthocyanin and dietary fiber. This innovation is expected to provide an alternative functional food for consumers with gluten intolerance while increasing the nutritional value of noodle products. Three formulation variations were tested, namely with the addition of purple sweet potato flour of 100 g, 125 g, and 150 g, while the amount of tapioca and rice flour was maintained at 100 g each, and the addition of 225 mL of water and 4 g of salt. Organoleptic quality assessment was carried out by 35 panelists using parameters of color, shape, aroma, texture, and taste, which were then analyzed using one-way analysis of variance (ANOVA) and Duncan's follow-up test to determine significant differences between treatments. The results showed that the best formulation was obtained from a combination of 100 g tapioca, 100 g rice flour, and 150 g purple sweet potato flour. The resulting noodle product has an attractive dark purple color, a fairly straight and long shape (>30 cm), a distinctive purple sweet potato aroma, a fairly chewy and elastic texture, and a savory taste with purple sweet potato nuances. Laboratory tests on the best samples showed prominent nutritional content, namely 59.81% carbohydrates, 3.88% dietary fiber, 6.82% protein, 31.90 mg anthocyanin/100 g, 3.71% fat, 24.50% water content, and 0.21% ash. With these organoleptic characteristics and nutritional composition, this gluten-free wet noodle product has the potential to be a healthy and functional alternative food, especially for individuals who require a gluten-free diet. This research also opens up opportunities for the development of noodle products based on local ingredients that are highly nutritious and have a selling value.